Web-Based Facilities and Infrastructure Management Information System Using the Waterfall Method at Singosari Private Elementary School - Hardianti, Eva; Ginting, Subhan Hafiz Nanda; Ruziq, Fahmi (Journal of Technology and Computer, 2026)
The management of facilities and infrastructure at Singosari Private Elementary School currently faces various challenges due to the manual nature of the process. This manual system causes several problems, including difficulties in accurately tracking the condition of assets, slow data retrieval, and the risk of data loss or corruption. To address these issues, this study aims to design and develop a computerized, web-based facility and infrastructure management information system. The system’s development employs the Waterfall method, which includes the following stages: requirements analysis, system design, code implementation, testing, and maintenance. The system is designed to be easily accessible via a web browser, making it convenient for users to manage data from anywhere within the school environment. The result of this research is a functional, web-based information system application that can be implemented to manage facilities and infrastructure at Singosari Private Elementary School.